Altered atrial cytosolic calcium handling contributes to the development of postoperative atrial fibrillation. Issue 7 (10th June 2020) - Fakuade, Funsho E; Steckmeister, Vanessa; Seibertz, Fitzwilliam; Gronwald, Judith; Kestel, Stefanie; Menzel, Julia; Pronto, Julius Ryan D; Taha, Karim; Haghighi, Fereshteh; Kensah, George; Pearman, Charles M; Wiedmann, Felix; et al.
Abstract: Aims : Atrial fibrillation (AF) is a commonly occurring arrhythmia after cardiac surgery (postoperative AF, poAF) and is associated with poorer outcomes. Considering that reduced atrial contractile function is a predictor of poAF and that Ca 2+ plays an important role in both excitation–contraction coupling and atrial arrhythmogenesis, this study aims to test whether alterations of intracellular Ca 2+ handling contribute to impaired atrial contractility and to the arrhythmogenic substrate predisposing patients to poAF. Methods and results : Right atrial appendages were obtained from patients in sinus rhythm undergoing open-heart surgery. Cardiomyocytes were investigated by simultaneous measurement of [Ca 2+ ]i and action potentials (APs, patch-clamp). Patients were followed-up for 6 days to identify those with and without poAF. Speckle-tracking analysis of preoperative echocardiography revealed reduced left atrial contraction strain in poAF patients. At the time of surgery, cellular Ca 2+ transients (CaTs) and the sarcoplasmic reticulum (SR) Ca 2+ content were smaller in the poAF group. CaT decay was slower in poAF, but the decay of caffeine-induced Ca 2+ transients was unaltered, suggesting preserved sodium-calcium exchanger function. In agreement, western blots revealed reduced SERCA2a expression in poAF patients but unaltered phospholamban expression/phosphorylation. Computational modelling indicated that reduced SERCA activity promotes occurrence of CaT and AP alternans. Indeed, alternans of CaT and AP occurred more often and at lower stimulation frequencies in atrial myocytes from poAF patients. Resting membrane potential and AP duration were comparable between both groups at various pacing frequencies (0.25–8 Hz). Conclusions : Biochemical, functional, and modelling data implicate reduced SERCA-mediated Ca 2+ reuptake into the SR as a major contributor to impaired preoperative atrial contractile function and to the pre-existing arrhythmogenic substrate in patients developing poAF. Graphical Abstract: